Pengaruh Metode Silaba Berbantuan Multimedia Interaktif Terhadap Kemampuan Membaca Permulaan - Jannah, Choirun Ni'matul; Madyawati, Lilis; Mardiana, Tria (Borobudur Educational Review, 2026)
This study aimed to analyze the effect of the syllabic method integrated with interactive media on the early reading skills of first-grade elementary school students. The research employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest design. The participants consisted of all 15 first-grade students at Langgeng State Elementary School of Temanggung. Data were collected through an oral reading test designed to assess students' early reading skills. Data analysis was conducted using the Shapiro–Wilk normality test and hypothesis testing through a Paired Sample t-test. The results revealed a significance value of 0.000 (< 0.05), indicating a statistically significant difference between students' early reading skills before and after the treatment. Therefore, the implementation of the syllabic method supported by interactive media was proven to have a significant positive effect on improving the early reading skills of first-grade students at SDN Langgeng Temanggung.